The effects of nitric oxide donors and inhibitors on neutrophil functions in Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2002)
Objective. The effects of nitric oxide donor SNAP and nitric oxide inhibitors L-NMMA and AG on the functions of neutrophils in patients with Behcet's Disease (BD) were investigated in vitro. Methods. Oxidative burst and phagocytosis of neutrophils were evaluated by flow cytometry in patients with Behcet's disease (n = 32), inflammatory (n = 17) and healthy controls (n = 14), in the presence of L-NMMA, AG and SNAP. Results. The stimulation index of oxidative burst was found to be significantly decreased following PMA stimulation in patients with active BD compared to inflammatory and healthy controls. Oxidative function of neutrophils were inhibited in all 3 groups in the presence of L-NMMA, AG and SNAP L-NMMA inhibited the oxidative burst of neutrophils obtained from healthy controls more than inflammatory controls and BD (80% vs 52% and 53% respectively, p = 0.001). No significant difference of phagocytosis inhibition was found with L-NMMA, AG and SNAP and there were also no differences between the groups (% 9-39). Conclusion. Nitric oxide donors and inhibitors may have a therapeutic role in Behcet's disease by suppresing neutrophil activity.
Keywords: Behcet's disease; nitric oxide; neutrophils; BLOOD; PHAGOCYTOSIS; HLA-B51